Can adults with low literacy understand shared decision making questions? A qualitative investigation. Issue 11 (November 2016) - Muscat, Danielle M.; Shepherd, Heather L.; Morony, Suzanne; Smith, Sian K.; Dhillon, Haryana M.; Trevena, Lyndal; Hayen, Andrew; Luxford, Karen; Nutbeam, Don; McCaffery, Kirsten
Highlights: Questions to support SDM were difficult for adults with low literacy/poor English. AskShareKnow question-set was easier for participants. Clarification of terms using a structured response was reasonably effective. Participants perceived questions as useful but identified barriers to use. SDM question-sets alone are not sufficient to support SDM for these adults. Abstract: Objective: Participation in shared decision-making (SDM) may be difficult for adults with lower literacy. Tools to support consumers to engage in SDM are rarely designed for or evaluated with adults with lower literacy and/or poor English language. Methods: Qualitative interviews were conducted with 26 adults with lower literacy and/or poor English language skills to investigate (a) whether participants where able to read and understand two generic SDM consumer support tools (Smart Health Choices and AskShareKnow question-sets), (b) which question-set was easier for participants and, (c) perceived usefulness of the question-sets and barriers to use. Interviews were analysed using Framework Analysis. Results: Participants had difficulties understanding terms embedded within both the AskShareKnow and Smart Health Choices questions. Our findings suggest that the AskShareKnow question-set was easier for our participants than the Smart Health Choices questions, and clarification using a structured response was reasonably effective. While participants appreciated the usefulness of the questions, they identified important barriers to use. Conclusions: Generic question-sets alone are not sufficient to support SDM for adults with lower literacy and/or poor English-language skills. Practice implications: To ensure that SDM is accessible to all, we must consider how best to support adults with low literacy and/or poor English-language skills to participate in this process.